Construct Data of Foundation Patterns of Clothing for Product Development of Small and Medium-Sized Garment Company in Vietnam - Nguyen, Thi Thuy Ngoc; Ho, Thi Nhu Quynh (Old Journal, 2018)
In this study, the list of foundation patterns of clothing has been proposed to serve the product development of ready-to-wear garment in small and medium-sized garment company in Vietnam. Garment manufacturers can select the list of needed foundation patterns depending on customer groups or markets and types of products. This paper presents the results of the development of the support program using the Wizard tool of AccuMark software that allows to automatically draw the foundation patterns of clothing and results of data construction of foundation patterns of clothing with SEV clothing construction systems. With this program, every manufacturer can easily obtain the necessary foundation patterns to fit their customer groups by changing dimension parameters of human body sizes and design parameters.